Building a Sustainable Performance Evaluation System for Educators and School Staff - Sofyan Rosidi; Siti Aimah (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
This study aims to analyze and reconstruct the performance appraisal system for educators and educational staff into a sustainable performance appraisal system at Madrasah Islamiyyah Manba'ul Huda Kabat in Banyuwangi. This study employs a qualitative approach with a case study design to analyze the development of a sustainable performance appraisal system at Madrasah Islamiyyah Manba'ul Huda in Kabat, Banyuwangi. The research was conducted over a period of one month through non-participant observation, semi-structured in-depth interviews, and a review of documents involving four informants selected through purposive sampling: the madrasah principal, the vice principal for curriculum, a senior teacher, and the administrative head. Data were analyzed using the Miles, Huberman, and Saldaña interactive model through the stages of open coding, axial coding, and selective coding, while data validity was strengthened through triangulation and member checking. The results of the study indicate that the performance appraisal system at Madrasah Islamiyyah Manba'ul Huda Kabat Banyuwangi has transformed from an administrative performance appraisal toward a sustainable performance appraisal system. This transformation was achieved through the reconstruction of a sustainability-based appraisal system, the implementation of continuous feedback, and the integration of appraisal results with professional competency development. These three elements form a performance management cycle that fosters reflection, learning, and the continuous enhancement of human resource capacity. This study reinforces the concept of sustainable performance appraisal by positioning appraisal as a strategic instrument in organizational learning and human resource development, and provides practical implications for managing a performance appraisal system that is more adaptive, collaborative, and oriented toward improving the quality of education.